Xanthine Oxidase inhibitory activity from potential Malaysian medicinal plants as remedies for gout - Azmi, Saiful Mohammad Nizam; Jamal, Parveen; Amid, Azura (2010)
Malaysia has a rich diversity of medicinal plants and some of them have the property to inhibit xanthine oxidase (XO), which can be introduced as new natural source of gout medication and a substitute for synthetic xanthine oxidase inhibitors (XOI), specifically Allopurinol which has many side effects. Fifty samples from twenty plant species were examined for XO inhibitory activity. Selection of plants was based on their frequent usages by local folks for their medicinal benefits and activities in three different extraction solvents; distilled water, 70% methanol, 100% ethanol. The degree of XO inhibition was determined by measuring the absorbance spectrophotometrically at 295 nm associated with uric acid formation. Ninety-nine percent of the crude extracts were found to have XO inhibitory activity at 100 μg/ml, and 57% showed greater than 50% inhibition. On the basis of availability and sustainability, distilled water extract of Carica papaya leaves was selected for optimization of process conditions, namely, extraction temperature (⁰C), extraction time (hour), agitation speed (rpm), and ratio of sample to the solvent (1 g/ml) using Central Composite Design (CCD) of Response Surface Methodology (RSM) from Design Expert© v.6.0.8 software. The analysis revealed that the maximum %XOI activity can be reached with these conditions: 30⁰C, 17 hour, 125 rpm and 1g/19ml. The optimized conditions were verified and the maximum %XOI obtained was 86.93%, lower 7% yet comparable to the activity exhibited by Allopurinol but safer and less cost incurred.